Thermospheric nitric oxide energy budget during extreme geomagnetic storms: a comparative study - Bag, Tikemani; Kataoka, R.; Ogawa, Y.; Fujiwara, H.; Li, Z.; Singh, Vir; Sivakumar, V.; Sridharan, S.; Pirnaris, P.; Tourgaidis, T. (Frontiers in Astronomy and Space Sciences, 2024)
We selected three super storms (Dst index less than -350 nT) of year 2003-04 to study the thermospheric energy budget with a particular emphasis on the thermospheric cooling emission by Nitric Oxide via 5.3µm wavelength. The Nitric Oxide radiative emission data are obtained from sounding of atmosphere by broadband emission radiometry (SABER) instrument onboard the thermosphere ionosphere mesosphere energetics and dynamics (TIMED) satellite and the thermosphere ionosphere electrodynamic general circulation model (TIEGCM) simulation. Different energy sources for the magnetospheric energy injection and the thermospheric/ionospheric dissipation processes are calculated using empirical formulations, model simulations and space borne and ground-based measurements. The Joule heating rates calculated from different sources show similar variations but significant difference in the magnitude. The Nitric Oxide cooling power is calculated by zonally and meridionally integrating the cooling flux in the altitude range of 100-250 km. The satellite observed cooling flux responds faster to the energy input as compared to the modeled results. The cooling power increases by an order of magnitude during storm time with maximum radiation observed during the recovery phase. Both the satellite observed and modeled cooling powers show strong positive correlation with the Joule heating power during main phase of the storm. It is found that the maximum radiative power does not occur during the strongest storm, and it strongly depends on duration of the main phase. The model simulation predicts a higher cooling power as compared to the observation. During a typical superstorm, on average 1.87×10 5 GW cooling power exiting thermosphere is estimated by the TIEGCM simulation. On average it is about 40% higher than the satellite observation.